Un exemple de rayonnement universitaire occidental en Europe centrale et orientale : étude de cas sur les enseignants français embauchés à l’université roumaine de Cluj après 1919 - Ana-Maria Stan (Les Cahiers de Framespa)
Summary: This research analyzes an important part of the French university presence abroad in the first half of the XXth century, namely the assistance brought to the scientific and institutional development of the Central European universities after the retracement of the borders and the political changes which took place in this area at the end of the First World War. It is a case study on the career of several French academics who came to work at the Romanian university of Cluj, in Transylvania, an institution which opened its doors since 1919. Using short portraits, we recall the professional path of four French teachers during their stay in Romania, in Cluj, and their interactions with this host country.